2010
DOI: 10.1007/s00280-010-1433-7
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of biweekly docetaxel and S-1 combination chemotherapy as first-line treatment for advanced gastric cancer

Abstract: S-1 plus docetaxel combination therapy in an outpatient setting provided promising activity with acceptable adverse toxicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The median PFS was 6.5 months and median OS was 15.3 months. Twenty-four patients (53.3 %) received second-line chemotherapy [16]. In present study, PFS and OS were comparable with docetaxel plus S-1 regimen, but more patients received second-line chemotherapy.…”
Section: Discussionsupporting
confidence: 47%
“…The median PFS was 6.5 months and median OS was 15.3 months. Twenty-four patients (53.3 %) received second-line chemotherapy [16]. In present study, PFS and OS were comparable with docetaxel plus S-1 regimen, but more patients received second-line chemotherapy.…”
Section: Discussionsupporting
confidence: 47%
“…Indeed, the current trend among most research groups is to develop strategies to individualize the use of chemotherapy in older or frail patients. Thus, trials have been conducted regarding modified oxaliplatin-based, two-drug chemotherapies(21-23) and double-agent schedules with docetaxelfluoropyrimidine (24).The feasibility of using an attenuated, three-agent scheme denominated miniDOX (reduced dose docetaxel-oxaliplatin-capecitabine) has also been evaluated in frail, older people (25). In general, all these experiences have concluded that modified schedules are efficacious and convenient in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Each course lasted 1 month. Treatment was continued until disease progression, patient refusal or unacceptable toxicity occurred, as shown in the previous study [3]. The mean numbers of DS treatments (±SD) were 4.8 ± 2.7 (range 2–13) in 83 registered patients and 3.3 ± 1.7 (range 2–8) in 71 patients without gastrectomy.…”
Section: Methodsmentioning
confidence: 99%
“…This retrospective study included the patients in our previous phase II study [3] and a similar population treated with the same regimen. The patients were aged 37–91 years (mean ± SD = 67.7 ± 7.4), and all were preoperatively diagnosed as having gastric adenocarcinoma using imaging tools following analysis of endoscopic biopsies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation